2019
DOI: 10.1017/s0950268819000943
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence analysis of human norovirus GII.17 detected in South Korea

Abstract: Norovirus, a major cause of gastroenteritis in people of all ages worldwide, was first reported in South Korea in 1999. The most common causal agents of pediatric acute gastroenteritis are norovirus and rotavirus. While vaccination has reduced the pediatric rotavirus infection rate, norovirus vaccines have not been developed. Therefore, prediction and prevention of norovirus are very important. Norovirus is divided into genogroups GI–GVII, with GII.4 being the most prevalent. However, in 2012–2013, GII.17 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition, one strains (Norozj-9) isolated in this study belonged to GII.17. The GII.17 genotype was rarely detected in human populations globally in the past, but a new GII.17 variant associate with sporadic acute gastroenteritis cases was frequently detected in China and some south-eastern Asian countries in late 2014 ( Pan et al., 2016 ; Zhang et al., 2016 ; Kim et al., 2019 ; Motoya et al., 2019 ; Chen et al., 2020 ). Here, few sequence reads of GII.17 in library 9 indicated that it was not the predominant genotype in causing acute gastroenteritis outbreaks but accounted for sporadic diarrhea cases in Jiangsu of China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one strains (Norozj-9) isolated in this study belonged to GII.17. The GII.17 genotype was rarely detected in human populations globally in the past, but a new GII.17 variant associate with sporadic acute gastroenteritis cases was frequently detected in China and some south-eastern Asian countries in late 2014 ( Pan et al., 2016 ; Zhang et al., 2016 ; Kim et al., 2019 ; Motoya et al., 2019 ; Chen et al., 2020 ). Here, few sequence reads of GII.17 in library 9 indicated that it was not the predominant genotype in causing acute gastroenteritis outbreaks but accounted for sporadic diarrhea cases in Jiangsu of China.…”
Section: Discussionmentioning
confidence: 99%
“…SaV infections are responsible for both sporadic cases and occasional outbreaks of acute gastroenteritis. The prevalence rate for SaV was 6.5% in low and middle income countries ( Kim et al., 2019 ). SaV GI was the dominant genogroup globally.…”
Section: Discussionmentioning
confidence: 99%